2022
DOI: 10.1891/rtnp-d-21-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Transtheoretical Model-Based Foot Care Program in Improving Foot Care Behaviors and Self-Efficacy in Adults With Type 2 Diabetes

Abstract: This study aimed to evaluate the effects of a transtheoretical model (TTM)-based foot care program on foot self-care behaviors and self-efficacy among adults with type 2 diabetes (T2DM). A prospective, assessor-blinded, randomized controlled trial was conducted between January 2020 and October 2020 at the endocrinology outpatient unit of a hospital in the north-west Turkey. The sample was composed of 51 adults with T2DM randomly allocated to the intervention group (n = 25) and control group (n = 26). The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The 29 eligible RCTs included 3891 participants from 16 countries, with sample sizes of 40 to 749 participants, and had follow-up durations ranging from 2 weeks to 26 months. Five studies recruited participants with active foot ulcers, 25,32,37,48,49 six trials included past ulcer amongst the inclusion criteria, 30,33,35,36,40,45 one trial included participants with ESRF and in the remaining trials the reporting of inclusion and exclusion criteria was very limited but did suggest high-risk participants were included (Table 1 and Table S2). Overall 12 trials were considered to have included participants at high risk of DFD [25][26][27]30,32,[34][35][36][37][38]40,48,49 (Table 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 29 eligible RCTs included 3891 participants from 16 countries, with sample sizes of 40 to 749 participants, and had follow-up durations ranging from 2 weeks to 26 months. Five studies recruited participants with active foot ulcers, 25,32,37,48,49 six trials included past ulcer amongst the inclusion criteria, 30,33,35,36,40,45 one trial included participants with ESRF and in the remaining trials the reporting of inclusion and exclusion criteria was very limited but did suggest high-risk participants were included (Table 1 and Table S2). Overall 12 trials were considered to have included participants at high risk of DFD [25][26][27]30,32,[34][35][36][37][38]40,48,49 (Table 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Of 2424 unique records identified from the search strategy, 74 underwent full‐text review, and 29 were found to be eligible for inclusion (Figure 1 and Table ) 21–49 . The 29 eligible RCTs included 3891 participants from 16 countries, with sample sizes of 40 to 749 participants, and had follow‐up durations ranging from 2 weeks to 26 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations